Large‐Scale Synthesis of Crystalline 1, 2, 3, 4, 6, 7‐Hexa‐O‐acetyl‐L‐glycero‐α‐D‐manno‐heptopyranose1. Issue 12 (10th March 2015) - Stanetty, Christian; Baxendale, Ian R.
Abstract: The higher‐carbon sugarL ‐ glycero ‐D ‐ manno ‐heptose is a major constituent of the inner core region of the lipopolysaccharide (LPS) of many Gram‐negative bacteria. All preparative routes used to date require multiple steps, and scalability has been rarely addressed. Here a highly practical synthesis of crystalline 1, 2, 3, 4, 6, 7‐hexa‐ O ‐acetyl‐L ‐ glycero ‐α‐D ‐ manno ‐heptopyranose by a simple four‐step sequence starting fromL ‐lyxose is disclosed. Only two recrystallisations are required and the process was demonstrated on a >100 mmol scale, yielding 41 g of the target compound. Abstract : A practical synthesis of crystalline 1, 2, 3, 4, 6, 7‐hexa‐ O ‐acetyl‐L ‐ glycero ‐α‐D ‐ manno ‐heptopyranose in four simple steps fromL ‐lyxose is disclosed. The process requires only two recrystallisations and was demonstrated on a >100 mmol scale, allowing rapid access to this important bacterial sugar building block in a convenient storage form.